2019
DOI: 10.1021/acs.jchemed.8b00898
|View full text |Cite
|
Sign up to set email alerts
|

Using the “Red Bottle” Experiment for the Visualization and the Fast Characterization of Gas–Liquid Mass Transfer

Abstract: This paper presents a demonstration of the visualization and the characterization of gas−liquid mass transfer in a small bubbly column. The aim is to show how simple experiments can be used to directly quantify mass transfer without the need of sophisticated probes or complex titrations. The method here proposed is based on the "red bottle" reaction, i.e., the reversible oxidation by oxygen of dihydroresorufin to red resorufin. This reaction produces a distinctive red color, and in the specific condition ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…To calculate the overall volumetric mass transfer coefficient, k L -Áa, simply and directly, it was assumed in a first step that C Ã O 2 L , and k L Áa were kept constant during the whole mass transfer process and using the average gas-liquid hydrodynamics, e.g., hU B i. From the stoichiometry of dihydroresorufin and O 2 , two moles of DH react with one mole of O 2 , and the relationships between C O 2 L ðXÞ and the resazurin concentration are (Dietrich et al, 2019):…”
Section: Average Overall Volumetric Mass Transfercoefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate the overall volumetric mass transfer coefficient, k L -Áa, simply and directly, it was assumed in a first step that C Ã O 2 L , and k L Áa were kept constant during the whole mass transfer process and using the average gas-liquid hydrodynamics, e.g., hU B i. From the stoichiometry of dihydroresorufin and O 2 , two moles of DH react with one mole of O 2 , and the relationships between C O 2 L ðXÞ and the resazurin concentration are (Dietrich et al, 2019):…”
Section: Average Overall Volumetric Mass Transfercoefficientmentioning
confidence: 99%
“…(7). Various authors (Dietrich et al, 2019;Yang et al, 2017a) have found that the enhancement factor E is equal to 1 when the order of magnitude of k L was about 10 À4 m s À1 , typically in millireactors. Therefore, E was considered equal to 1 here.…”
Section: Average Overall Volumetric Mass Transfercoefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid phase consisted of solutions containing D-glucose anhydrous (Fischer-Scientific, CAS 50-99-7), sodium hydroxide (VWR, CAS1310-73-2) and resazurin (Sigma Aldrich, CAS 62758-13-8, molar mass 229.19 g mol -1 , purity 84%). This choice of liquid phase was motivated by the fact that this study was a preliminary work for implementing the colourimetric dye-based method proposed by Dietrich et al [39,40] to quantify the local gas-liquid mass transfer. The D- Table 2.…”
Section: Experimental Workmentioning
confidence: 99%
“…It is generally agreed that non-Newtonian fluids have complex rheological properties (e.g., shear thinning, viscoelasticity, etc.) leading to a variety of bubble shapes, such as teardrop or elongated bubbles [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%